VD_FINDINFO HC / 2022 / 942 vom 8. Dezember 2022 - VD Tribunal cantonal (2022)
CESSION DE CRÉANCECO, ILLICÉITÉ, REPRÉSENTATION EN PROCÉDURE, NULLITÉ | 164 al. 1 CO, 20 al. 1 CO, 59 al. 1 CPC (CH), 59 al. 2 let. a CPC (CH), 68 al. 2 CPC (CH)